2023
DOI: 10.5603/fm.a2022.0030
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography evaluation of origin, V2 segment variations and morphology of vertebral artery

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In the course of reviewing papers, we found an interesting issue that there were some differences in the rate of variation of vertebral artery inlet in various reports. The variability of anomalous entry level we found was 8.30%, compared to 12.5% in Republika Srpska 5 , 15.7% in Germany 6 , 5.75% in Isreal 7 , 7.0% of LV and 6.2% of RV in Japan 8 , 8.7% in Taiwan, R.O.C 9 , 5.3% of LV and 0.8% of RV in Thailand 10 , 5.1% in Korea 11 , 8%of LV and 6.6% of RV in another study of Korea 12 , 7.5% of LV in Turkey 13 . This could be explained by sample sizes and structure differences.…”
Section: Discussionmentioning
confidence: 84%
“…In the course of reviewing papers, we found an interesting issue that there were some differences in the rate of variation of vertebral artery inlet in various reports. The variability of anomalous entry level we found was 8.30%, compared to 12.5% in Republika Srpska 5 , 15.7% in Germany 6 , 5.75% in Isreal 7 , 7.0% of LV and 6.2% of RV in Japan 8 , 8.7% in Taiwan, R.O.C 9 , 5.3% of LV and 0.8% of RV in Thailand 10 , 5.1% in Korea 11 , 8%of LV and 6.6% of RV in another study of Korea 12 , 7.5% of LV in Turkey 13 . This could be explained by sample sizes and structure differences.…”
Section: Discussionmentioning
confidence: 84%
“…The type 3b2 variation was reported in 1 of 4000 patients in the Indian population and 1.2% of the Jordanian population versus 0.1% in this study [ 1 , 14 ]. Origination of the vertebral artery directly from the aortic arch is important in endovascular interventions for the diagnosis and treatment of posterior cerebral events [ 16 , 27 ]. The type 3b7 variation was reported by Natsis et al in only one patient [ 13 ], and Mustafa et al found this aberrant configuration in two (0.4%) individuals [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, the human brain consists of two segments with separate arterial systems. The posterior part of the brain is nourished by the left vertebral artery and the right vertebral artery 1,2 . A portion of the cerebral blood flow is provided by the vertebral arteries (VAs) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A portion of the cerebral blood flow is provided by the vertebral arteries (VAs) 3 . The infratentorial structures of the brain (e.g., the cerebellum and the medulla) depend mainly on the VAs 3,1 . The VAs are originally divided from the first cervical part of the subclavian artery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation